Performance evaluation of a self‐administered home oral glucose tolerance test kit in a controlled clinical research setting. Issue 7 (26th April 2019) - Dunseath, G. J.; Bright, D.; Jones, C.; Dowrick, S.; Cheung, W.‐Y.; Luzio, S. D.
Abstract: Aim: To evaluate the performance of the current, pre‐production version of a novel home oral glucose tolerance test (Home OGTT) device when administered by trained research nurses, compared with a reference laboratory glucose analyser and a second laboratory analyser, incorporating a sample processing delay to simulate normal practice. Methods: One hundred women (aged 19–48 years), with and without known glucose intolerance were recruited. Following an overnight fast, participants attended for a 75‐g OGTT. A fasting capillary sample was applied to the Home OGTT device with a corresponding venous sample collected and measured immediately on the reference YSI 2300 stat plus analyser, and following a 1‐h delay on the Randox Daytona Plus analyser. The sampling process was repeated 2 h after the oral glucose load. Results: Some 97% of tested devices gave complete data for analysis. Good agreement was observed between the reference glucose analyser and the Home OGTT device, with the Home OGTT device displaying a small negative bias (−0.18 mmol/l, −1.75 to 1.39 mmol/mol; −1.0%, −26.4% to 24.5%; absolute and relative mean, 95% limits of agreement). When classified as normal glucose tolerant or glucose intolerant, the Home OGTT device showed 100% and 90% sensitivity, and 99% and 99% specificity using fasting plasma glucose and 2‐h glucose respectively. Similar sensitivity (100% and 100%) and specificity (96% and 99%) for fasting plasma glucose and 2‐h glucose were observed using the secondary analyser. Conclusions: The novel Home OGTT device was reliable and easy to use and showed excellent agreement with two separate laboratory analysers. The Home OGTT offers potential as an effective alternative for clinic‐based OGTT testing. What's new?: This study evaluates the performance of a novel, pre‐production version of a home oral glucose tolerance testing (Home OGTT) device. The device was easy to use, with an excellent device success rate and showed good agreement with two separate laboratory analysers in both normal glucose tolerance and glucose intolerance. Our findings demonstrate that the device offers an alternative to clinic‐based OGTT testing, with the potential for the test to be performed conveniently at home or in a community setting.